The chronology and tectonic style of landscape evolution along the elevated Atlantic continental margin of South Africa resolved by joint apatite fission track and (U‐Th‐Sm)/He thermochronology. Issue 3 (4th March 2016) - Wildman, Mark; Brown, Roderick; Beucher, Romain; Persano, Cristina; Stuart, Fin; Gallagher, Kerry; Schwanethal, James; Carter, Andrew
Abstract: Atlantic‐type continental margins have long been considered "passive" tectonic settings throughout the entire postrift phase. Recent studies question the long‐term stability of these margins and have shown that postrift uplift and reactivation of preexisting structures may be a common feature of a continental margin's evolution. The Namaqualand sector of the western continental margin of South Africa is characterized by a ubiquitously faulted basement but lacks preservation of younger geological strata to constrain postrift tectonic fault activity. Here we present the first systematic study using joint apatite fission track and apatite (U‐Th‐Sm)/He thermochronology to achieve a better understanding on the chronology and tectonic style of landscape evolution across this region. Apatite fission track ages range from 58.3 ± 2.6 to 132.2 ± 3.6 Ma, with mean track lengths between 10.9 ± 0.19 and 14.35 ± 0.22 µm, and mean (U‐Th‐Sm)/He sample ages range from 55.8 ± 31.3 to 120.6 ± 31.4 Ma. Joint inverse modeling of these data reveals two distinct episodes of cooling at approximately 150–130 Ma and 110–90 Ma with limited cooling during the Cenozoic. Estimates of denudation based on these thermal histories predict approximately 1–3 km of denudation coinciding with two major tectonic events. The first event, during the Early Cretaceous, was driven by continental rifting and the development and removal of synrift topography. The second event, during the Late Cretaceous, includes localized reactivation of basement structures as well as regional mantle‐driven uplift. Relative tectonic stability prevailed during the Cenozoic, and regional denudation over this time is constrained to be less than 1 km. Key Points: First joint apatite fission track and (U‐Th)/He data for the southwest African continental margin Present‐day topography due to kilometer‐scale erosion that occurred during the Cretaceous Faulting onshore as well as regional uplift of the margin inferred during the Middle to Late Cretaceous